DINAMIKA PROFESI GURU: CITRA, HARAPAN, DAN TANTANGAN - Imam Suraji (LPMPP Universitas Negeri Yogyakarta, 2008)
Teacher is one of the major key holderin the success of education.process andstudy in school. Teachermust beresponsible professionally to parents, society, andnation. That is so strategic that the role of teacher for nation future, teacher shouldnot be asa· secondary profession, but as first profession that it's just believed tothemwho can fulfill the needed requirement. In daily life, teacher is expected to beableto be the function as a model for society (digugu Zan ditiru). That expectation isa challenge for teacher. To be able to fulfill· that· expectation, teachermust haveteacher profession competence. Teachermust be expert on his major,understandingthe science of·education, having good characteristic, attitude, andbehavior, and also good in communicating with alldirections related with their job.Other requirement that is not less important is to believe,and God fearing, and alsobe· able to practice all thatare taught in daily life.